Pengembangan Sistem Informasi Akademik Siswa Pada Sekolah Berbasis Asrama (Studi Pada Tazkia International Islamic Boarding School Malang) - Dhimas Pristian Alamsyah Putra; Yusi Tyroni Mursityo; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Tazkia International Islamic Boarding School (IIBS) is a religious-based non-formal school that implement a boarding system. The student report making process at Tazkia IIBS is done using a module called the teacher kit that used by the teacher to record their student's academic scores. Academic scores that have been recorded into the teacher kit must be reported to academic section every three months to get verified. At the end of the semester, the scores will calculated and assessed by the teacher to create the student report cards. All this processes considered to be less efficient because it requires a long time and a long stage to create a student report card. With these problem, a solution is needed, one of which is by developing a Student Academic Information System. In this research, it was explained the developing process of Student Academic Information System on Tazkia IIBS, that aimed to dealing with the student report cards making process issue. The development of this information system is using the Rational Unified Process (RUP) method. RUP method is an object-based system development method consisting of four stages, namely inception, elaboration, construction, and transition. This method was chosen because it is able to carry out an iterative development process and allows to handle the requirement changing. The system which has been developed, is tested using validation testing with valid result on all test cases, as well as compatibility tasting was performed to tests the non-functional requirement of the system with some minor issue in several web browsers. The user acceptance testing generated acceptance rate of 67% which indicate that the system has been built properly.